Indonesia : Advancing a National Disaster Risk Financing Strategy--Options for Consideration - World Bank (Washington, DC, 2015)
This study presents options for a national disaster risk financing strategy in Indonesia, drawing heavily on international experience. The study discusses a series of complementary options for a national disaster risk financing strategy, based on a preliminary fiscal risk analysis and a review of the current budget management of natural disasters in Indonesia. It benefits from the international experience of the World Bank, which has assisted several countries in the design and implementation of sovereign catastrophe risk financing strategies. The rehabilitation and reconstruction fund is the main budget instrument for the Government of Indonesia (GoI) to finance public post-disaster expenditures, but it is under-capitalized. This study presents an optimal combination of risk-retention and risk transfer instruments that could help the GoI increase its immediate financial response capacity against natural disasters and better protect its fiscal balance. Building on the three-tier risk layering approach promoted by the World Bank and the preliminary fiscal risk assessment analysis, the following financial strategy could be considered by the GoI. This strategy would provide the GoI with access to immediate liquidity in the aftermath of a disaster at a competitive cost. The strategy would allow the GoI to access up to US$1.8 billion liquidity in the aftermath of a disaster in order to finance immediate post-disaster expenditures, such as grants for livelihood and low income housing reconstruction. Preliminary disaster fiscal risk assessment analysis shows that this would protect the GoI against disasters occurring every 100 years. The implementation of a national disaster risk financing strategy would require significant institutional capacity building.